2011
DOI: 10.1093/hmg/ddr076
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 neurotoxicity and protein aggregation modulated by heat shock factor and insulin/IGF-1 signaling

Abstract: TAR DNA-binding protein 43 (TDP-43) plays a key role in the neurodegenerative diseases including amyotrophic lateral sclerosis and frontotemporal lobar degeneration. The nature of the TDP-43-mediated neurotoxicity associated with these diseases is not yet understood. Here, we have established transgenic Caenorhabditis elegans models that express human TDP-43 variants in the nervous system, including the full-length wild-type (WT) and mutant proteins and a pathologic C-terminal fragment. The C. elegans models d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 70 publications
(87 reference statements)
6
111
4
Order By: Relevance
“…The cell death appeared non-apoptotic, because we observed no activation of caspase-3/7 during the 48-h cell culture (not shown). It was reported that C-terminal 25-or 35-kDa fragments, not containing RRM1, replicate TDP-43 proteinopathy in cells (28) and in vivo models (43,44). However, we found no relationship between the amount of these fragments (Fig.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The cell death appeared non-apoptotic, because we observed no activation of caspase-3/7 during the 48-h cell culture (not shown). It was reported that C-terminal 25-or 35-kDa fragments, not containing RRM1, replicate TDP-43 proteinopathy in cells (28) and in vivo models (43,44). However, we found no relationship between the amount of these fragments (Fig.…”
Section: Discussioncontrasting
confidence: 60%
“…TAR DNA-binding protein of 43 kDa (TDP- 43) 3 is a DNAand RNA-binding nuclear protein that has been identified as a core component of ubiquitinated inclusions in frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS) (1,2). Accumulating evidence suggests that TDP-43 proteinopathy mediates motor neuron degeneration in familial ALS caused by diverse genetic defects in ubiquilin 2, profilin 1, optineurin, valosin-containing protein, and C9ORF72 (reviewed in Ref.…”
Section: Cells Overexpressing the Rrm1-c/s Tdp-43 With Antibody Targementioning
confidence: 99%
“…147 In addition, pathogenic forms of TDP-43 expressed in C. elegans or Drosophila show slower exchange rates from aggregates or neuronal granules by FRAP. 127,148 Several reasons have been proposed as to why persistent stress granules or related mRNP aggregates could be toxic to cells. 136,144 Sequestration of protein factors in granules could lead to a reduced ability of granules to appropriately remodel mRNPs, and may limit the available pool of a protein that also functions elsewhere in the cell.…”
Section: Toxic Stress Granules As a Cause Of Degenerativementioning
confidence: 99%
“…Therefore, IIS reduction elevates stress resistance by hyperactivating DAF-16 and HSF-1 (Lithgow et al, 1995;Honda and Honda, 1999). This manipulation also extends lifespan and protects from proteotoxicity Morley and Morimoto, 2004;Cohen et al, 2006;Teixeira-Castro et al, 2011;Zhang et al, 2011), raising the question of whether these functions are mechanistically linked.…”
Section: Introductionmentioning
confidence: 99%